Air Annealing Facilitates Crystallization Reconstruction of Quasi‐2D Perovskite. Issue 3 (14th December 2022) - Wang, Boxin; Bi, Shiqing; Cheng, Qian; Huang, Gaosheng; Zhang, Weichuan; Han, Bing; Yang, Yingguo; Zhang, Yuan; Zhang, Hong; Zhou, Huiqiong
Abstract : Although the photovoltaic performance of perovskite solar cells (PSCs) has reached commercial standards, the processing environment of a purely inert gas atmosphere significantly increases the cost of installing manufacturing facilities in actual manufacturing plants and hinders their commercial mass production. The thermal annealing condition of quasi‐2D perovskite films can significantly affect the self‐assembly behavior of bulky organic cations, which modulates the phase distribution of 2D species with different n values. Herein, the properties of quasi‐2D perovskite annealing in a N2 versus an environment representative of industrial conditions, i.e., open‐air with 30% humidity are compared. It is found that the crystallization process of perovskites is regulated by air annealing, leading to high‐quality 2D perovskite films with reduced trap density, well‐aligned phase distribution, and released residual strain. The resulting devices prepared by air annealing achieve a power conversion efficiency of 18% with high reproducibility and suppressed voltage loss. The enhanced thermal stability of the air‐annealed films is proved by in situ grazing incidence wide‐angle X‐ray scattering. The combination of air annealing and simple planar structures would facilitate the mass production of PSCs. Abstract : The processing environment of perovskite solar cells in pure inert gas significantly increases the practical production cost. The thermal annealing atmosphere of quasi‐2D perovskite films can affect the self‐assembly behavior of bulky organic cations, which modulates the phase distribution of 2D species with different n values. Air annealing modulates the crystallization process, resulting in high‐quality quasi‐2D perovskite films.